Work insecurity and compensation on turnover intention mediated by the job satisfaction of employees - Brahmannanda, Satya; Dewi, IGA Manuati (International research journal of management, IT and social sciences, 2020)
Among the challenges companies must face is to reduce the intensity of employee turnover. Companies need to improve and implement policies that can minimize turnover. The purpose of this study is to examine and explain the influence of job insecurity, compensation, and job satisfaction on turnover intention and examine the mediating role of job satisfaction in the influence of job insecurity and compensation on turnover intention. This research is quantitative associative research conducted at PT. True Partner Style. The total population is 98 employees with a sample of 79 employees. The data were obtained through a questionnaire using the 5-point Likert scale. The data analysis technique used was SEM-PLS. The results revealed that job insecurity has a positive and significant influence on turnover intention, compensation and job satisfaction has a negative influence on turnover intention, job insecurity has a negative influence on job satisfaction, compensation has a positive influence on job satisfaction, and job satisfaction was able to partially mediate the influence of job insecurity and compensation on turnover intention.